2014
DOI: 10.4238/2014.july.24.13
|View full text |Cite
|
Sign up to set email alerts
|

Clinical three-dimensional conformal radiotherapy research using repeated computed tomography scans for field reduction in older non-small-cell lung cancer patients

Abstract: ABSTRACT. This study investigated the curative and toxic effects of three-dimensional conformal radiotherapy (3D-CRT), using repeated CT scans for field reduction in older non-small-cell lung cancer (NSCLC) patients. 3D-CRT was administered to 36 older patients with NSCLC, and irradiation fields included the primary lesion and metastatic lymph nodes. After CT localization scanning, images were fed into a treatment planning system to delineate the gross tumor volume (GTV)1 and prepare Plan 1. After the DT50 (do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…The most common cause of lung cancer is smoking and nearly 87% of lung cancer cases are caused by smoking. The NSCLC metastasis is reported as the most important cause leading to the failure of treatment (Fu et al, 2014). Chemotherapy, radiotherapy, and surgical treatment are widely used for NSCLC therapy.…”
Section: Introductionmentioning
confidence: 99%
“…The most common cause of lung cancer is smoking and nearly 87% of lung cancer cases are caused by smoking. The NSCLC metastasis is reported as the most important cause leading to the failure of treatment (Fu et al, 2014). Chemotherapy, radiotherapy, and surgical treatment are widely used for NSCLC therapy.…”
Section: Introductionmentioning
confidence: 99%
“…Efforts towards facilitating higher dose escalation by assessing tumor shrinkage during treatment have been made in NSCLC [ 9 , 11 15 ]; these studies reported the feasibility of adaptive therapy during radiation in terms of superior planning and tumor control [ 9 , 12 , 14 16 ]; however, Gillham et al [ 11 ] reached the opposite conclusions. Besides achieving controversial results, all of these studies evaluated patients who received replanned radiation therapy but had small sample sizes and did not select patients based on tumor response at mid-radiation therapy, such as stable disease, partial response (PR) and complete response (CR).…”
Section: Introductionmentioning
confidence: 99%
“…Lung cancer has become one of the most common malignant tumors worldwide, with the highest morbidity and mortality rates among males as well as the highest morality rate and the second highest morbidity rate among females. 1 , 2 In most cases, lung cancer originates from bronchial mucous epithelia or glands, for which non-small-cell lung cancer (NSCLC) accounts over 80%. 3 , 4 NSCLC is a worldwide health problem and a leading cause of cancer-related deaths.…”
Section: Introductionmentioning
confidence: 99%